Timed up and go test combined with self-rated multifactorial questionnaire on falls risk and sociodemographic factors predicts falls among community-dwelling older adults better than the timed up and go test on its own - Ibrahim, Azianah (J Multidiscip Healthc, 2017)
BACKGROUND: Early detection of falls risk among older adults using simple tools may assist in fall prevention strategies. The aim of this study was to identify the best parameters associated with previous falls, either the timed up and go (TUG) test combined with sociodemographic factors and a self-rated multifactorial questionnaire (SRMQ) on falls risk or the TUG on its own. Falls risk was determined based on parameters associated with previous falls. DESIGN: This was a retrospective cohort study. SETTING: The study was conducted in a community setting. PARTICIPANTS: The participants were 1,086 community-dwelling older adults, with mean age of 69.6±5.6 years. Participants were categorized into fallers and nonfallers based on their history of falls in the past 12 months. METHOD: Participants’ sociodemographic data was taken, and SRMQ consisting of five falls-related questions was administered. Participants performed the TUG test twice, and the mean was taken as the result. RESULTS: A total of 161 participants were categorized as fallers (14.8%). Multivariate logistic regression analysis showed that the model (χ(2)(6)=61.0, p<0.001, Nagelkerke R(2)=0.10) consisting of the TUG test, sociodemographic factors (gender, cataract/glaucoma and joint pain), as well as the SRMQ items “previous falls history” (Q1) and “worried of falls” (Q5), was more robust in terms of falls risk association compared to that with TUG on its own (χ(2)(1)=10.3, p<0.001, Nagelkerke R(2)=0.02). CONCLUSION: Combination of sociodemographic factors and SRMQ with TUG is more favorable as an initial falls risk screening tool among community-dwelling older adults. Subsequently, further comprehensive falls risk assessment may be performed in clinical settings to identify the specific impairments for effective management.